Ethics knowledge, attitudes, and experiences of tertiary care pediatricians in Ethiopia - Atnafu Mekonnen Tekleab; John D. Lantos (BMC Medical Ethics, 2022)
Abstract Background Pediatricians in developing countries face different ethical dilemmas than do doctors working in settings with more resources. There are very few studies from developing countries analyzing pediatricians’ knowledge and attitudes regarding the ethical dilemmas that arise in such settings. To address this gap, we explored the clinical ethical knowledge, attitude and experience of physicians who are working in the Department of Pediatrics and Child Health (DPCH) of St Paul’s Hospital Millennium Medical College (SPHMMC), Addis Ababa, Ethiopia. Study population All pediatric resident doctors and pediatric consultants who were working in the DPCH of SPHMMC in December, 2020. Method A structured pretested self-administered questionnaire was distributed to all 79 of the residents and consultants in the department during the period December 15–27, 2020. The questionnaire assessed the knowledge (23 questions), attitude (9 questions) and experiences (9 questions) of the study participants regarding a variety of bioethical issues. Data were analyzed using SPSS version 20.0 for windows. The mean, median, standard deviation, and interquartile range of respondents’ scores were determined and compared using Fisher’s exact test. Result A total of 59/79 (75%) physicians completed the questionnaire. The mean age of the participants was 30.7 ± 4.1 years. Thirty six (61.0%) were female. At the time of data collection, more than half (57.6%) served < 5 years as a physician. The mean ethics knowledge score of the respondents was 12.3 ± 2.34 out of 23 knowledge questions. The lowest and highest knowledge scores were 8 and 19 respectively. Scores were highest on questions about confidentiality (94.9% correct) and lowest on questions about genetic testing and diagnosis (13.6% correct). Only 13 (22.4%) physicians agreed with the practice of children should never be treated without consent of the parent. Conclusion Tertiary care pediatricians at one hospital in Ethiopia lack knowledge about current standards in bioethics. There is a need for more ethics education in this setting.